Robots [videorecording (DVD)] - Christensen, Casper, 1968-; Hines, Ant; Woodley, Shailene; Whitehall, Jack, 1988-; Postacchini, Emanuela; Rutherford, Nicholas, 1985-; Rust, Paul, 1981-; Sheckley, Robert, 1928-2005 (Decal, 2023)
Charles is a womanizer while Elaine is a gold digger. The duo learns humanity when forced to team up and pursue robot doubles of themselves.